ANALISIS PENGARUH VARIABEL MAKROEKONOMI TERHADAP INDEKS HARGA SAHAM PROPERTI DAN KEUANGAN DI INDONESIA - Bagas Satrio Wibisono; Dian Octaviani R (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
This research discusses the influence of macroeconomic variables on Property Stock Price Index (IHSProp) and Finance Stock Price Index (IHSKeu). Quantitative research analising an impact of independent variables such as BI rate, Inflation, Money Supply (M2), Exchange Rate (Rp/USD) on dependent variables which are IHSProp and IHSKeu. The data used is monthly data start from 2008: 1 until 2015: 12. The method used in this thesis is Error Correction Model (ECM). The results showed that four macroeconomic variables globally have significant impact on IHSProp and IHSKeu in either short and long term. In the short term BI rate significantly influences IHSKeu while exchange rate significantly influences IHSProp and IHSKeu. In the long term, Commodity inflation significantly influences IHSProp. Money Supply significantly influences on IHSProp and IHSKeu. Exchange rate significantly influences on IHSProp and IHSKeu.